2001
DOI: 10.1542/peds.108.4.e58
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for A New Variant of Measles-Mumps-Rubella–Induced Autism

Abstract: ABSTRACT. Objective. A link has been postulated between measles-mumps-rubella (MMR) vaccine and a form of autism that is a combination of developmental regression and gastrointestinal symptoms that occur shortly after immunization. This hypothesis has involved 3 separate claims: 1) that there is new phenotype of autism involving regression and gastrointestinal symptoms, 2) that this new variant is responsible for the alleged rise of autism rates, and 3) that this phenotype is associated with biological finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
188
3
7

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(207 citation statements)
references
References 32 publications
9
188
3
7
Order By: Relevance
“…In their report citing no evidence for a new variant of MMR-induced autism, Fombonne and Chakrabarti found no differences between regression and nonregression groups on symptom severity as measured by ADI scores, but they did report a difference in cognitive functioning that approached significance, with 46.1% of children in the regression group having an IQ<70 compared to 21.5% of the nonregression group (p=0.08, Fisher's exact test) (Fombonne & Chakrabarti, 2001). Brown and Prelock (1995) also reported that individuals with autism and regression had poorer social skills later in life compared to those with autism and no regression.…”
Section: Pervasivementioning
confidence: 95%
“…In their report citing no evidence for a new variant of MMR-induced autism, Fombonne and Chakrabarti found no differences between regression and nonregression groups on symptom severity as measured by ADI scores, but they did report a difference in cognitive functioning that approached significance, with 46.1% of children in the regression group having an IQ<70 compared to 21.5% of the nonregression group (p=0.08, Fisher's exact test) (Fombonne & Chakrabarti, 2001). Brown and Prelock (1995) also reported that individuals with autism and regression had poorer social skills later in life compared to those with autism and no regression.…”
Section: Pervasivementioning
confidence: 95%
“…In this large (n ¼ 473) sample, 17% of children were reported to have suffered from gastrointestinal symptoms lasting 3 months or more, and 25% were reported to have lost skills or regressed in their development, findings that are consistent with other epidemiological surveys. 11 No change over time was reported for both regression and occurrence of gastrointestinal symptoms, and results were similar for both typical and atypical forms of autism. Furthermore, the rates of both problems did not differ in children for whom parents first became concerned before the MMR immunization, as compared to those for whom parents became concerned after the MMR immunization.…”
mentioning
confidence: 81%
“…6 Several epidemiological investigations have tested the association between trends in rates of autism and either the introduction of measles-mumps-rubella (MMR) vaccine 7 or variations in MMR uptake, 8,9 and they all failed to demonstrate an association. Further analyses have examined whether or not regression in the course of autism 10,11 or health-seeking behavior by parents 12 clustered after MMR vaccination, and no evidence of time clustering was found. More recently, a large population-based cohort study of over 500,000 Danish children has shown no increase in the incidence of autism in children exposed to MMR compared to unexposed children.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional evidence includes primarily anecdotal reports, from parents noticing the onset of autism closely following immunization. Epidemiological evidence consistently does not support any correlation between the administration of the MMR vaccine and the incidence of autism (Chen, Landau, Sham, & Fombonne, 2004;Fombonne & Chakrabarti, 2001;Kaye, del Mar Melero-Montes, & Jick, 2001;Taylor et al, 1999), suggesting that anecdotal evidence may often be due to the concordance in the age of MMR vaccination and onset of autistic symptomatology. Another related theory is autism induced by neurotoxic levels of mercury, or from the presence of ethylmercury in the vaccine preservative thimerosal.…”
Section: Alternative Theoriesmentioning
confidence: 99%